Determination of Maintenance Planning Strategy On Pulverizer Boiler Machine Using Reliability Centered Maintenance (RCM) II Method (Case Study: PT. TJB Power Services) - Akhmad Syakhroni; Arifin Edo Kurniawan; Nuzulia Khoiriyah; M. Sagaf (Jurnal Rekayasa Sistem & Industri, 2021)
Continuous production causes machines to work without stopping which results in the risk of decreasingmachine productivity at PT. TJB Power Services. The company is an Operation and Maintenance companyfor PLTU Tanjung Jati B Units 1 and 2. In 2018, the level of Equivalent Availability Factor (EAF) Unit 1was 89.45% and Unit 2 was 93.76%, which was originally targeted at 100%. Meanwhile, in 2019 Unit 1increased to 95.60% and Unit 2 decreased to 88.12%. In general, the production process starts fromgrinding coal, which is used for fuel heating water into dry steam, which is flowing into a turbine to drive agenerator that produces electricity. Therefore, research was carried out in the pulverizer unit 2 because ithas decreased its availability and is a critical machine in the production process that will affect overallproductivity. Based on the RCM II analysis at the FMEA stage, the highest RPN value was obtained forcoal pipe and pyrite equipment. After analyzing with the Fishbone diagram, it is found that the root causesof failure include primary air and outside air containing seawater content and not coated with anti-rustresulting in corrosion, accumulating foreign objects that are not filtered in the silo and lack of maintenance.From the results of the analysis of these problems, it was found that the proposed improvements weremade in the form of the RCM II Decision Worksheet.